Urinary marker (MMP-9) and bladder cancer - Yaseen, Nahi Yousif (Iraqi Journal of Cancer and Medical Genetics, 2016)
Bladder cancer is a complex disease and this study of bladder cancer was conducted to assess the significance of level difference of MMP-9 in urine and tissue biopsy which has a role in tumor progression in bladder cancer patients. MMP-9 evaluated in urine of 48 bladder cancer patients and 40 healthy controls by ELISA test, and in 57 biopsies of bladder cancer and 40 normal urothelium (autopsies) by immunohistochemistry (IHC). Result indicated that urine MMP-9 showed high specificity in diagnosis bladder cancer patients, and has a role in discrimination between (newly diagnosed vs recurrence), but urine level and tissue expression of MMP-9 were unrelated to grade, muscle invasion. Some risk factors like Schistosomiasis and family history of cancer showed a significant association with MMP-9 tissue expression.